Rokeya from a comparative literary perspective - Hasan, Md. Mahmudul (The New Age, Dhaka, 2018)
IN MY doctoral study titled Introducing Rokeya’s Plural Feminism (University of Portsmouth, 2007), I sought to unearth the rich treasure of Rokeya Sakhawat Hossain’s (1880–1932) feminist writing and to compare it with that of two established English feminist writers, Mary Wollstonecraft (1759–1797) and Virginia Woolf (1882–1941), and two postcolonial ones Attia Hosain (1913-98) and Monica Ali (1967). My comparative study aimed at introducing Rokeya and her work to a wide-ranging readership and at revealing the relevance of her overarching feminist ideas to international feminisms beyond the borders of the South Asian subcontinent.